The Alien Citizen: Social Distance and the Economic Returns to Naturalization in the Southwest. (19th September 2021) - Catron, Peter
Abstract: Citizenship acquisition is often promoted as one factor that can facilitate the economic integration of immigrants. However, not all individuals and groups experience positive benefits from naturalization. This article argues that social distance from the native-born is an important factor that influences who does and does not benefit from citizenship acquisition. Specifically, I create a new continuous measure of social distance for immigrants during the age of mass migration. I show that the relationship between social distance and the economic returns to citizenship takes an inverted U-shape. Those considered closest and furthest away in social distance to the native-born report little to no advantages to citizenship, while those in the middle report larger returns. I then focus on the Mexican population in the historical Southwest and take advantage of a unique enumeration in the complete count 1930 U.S. census that coded Mexicans as either white or Mexican. Mexicans coded as white report economic differences between citizenship statuses, while Mexicans coded as nonwhite report no difference between citizenship statuses. The results suggest that citizenship may not be beneficial to all individuals and groups, depending on where they fall in the ethnoracial hierarchy.